Effects of the methanol fraction of modified Seonghyangjeongki-san water extract on transient ischaemic brain injury in mice. (1st January 2021) - Kang, Eun-Jin; Cho, Suin; Lim, Chiyeon; Lee, Byoungho; Kim, Young Kyun; Kim, Kyoung-Min
Abstract: Context: Recently in Korean medicine, the antioxidant and anti-inflammatory activities of Seonghyangjeongki-san (SHJKS) were reported. However, studies on the specific mechanisms of action of SHJKS for the treatment of ischaemic stroke are still lacking. Objective: This study investigates the mechanism of action of the water extract methanol fraction of modified SHJKS (SHJKSmex) on cerebral ischaemic injury. Materials and methods: C57BL/6 male mice were orally administered SHJKSmex (30, 100, or 300 mg/kg) for 3 consecutive days (2 days, 1 day, and 1 h, respectively) before middle cerebral artery occlusion (MCAO). Twenty-four hours after MCAO, the infarct volumes were measured, brain edoema indices were calculated, and neurological deficit scores were determined. Inflammation-related substances in the ipsilateral hemisphere were determined by western blotting, dichlorofluorescin diacetate, thiobarbituric acid-reactive substances assay, and enzyme-linked immunosorbent assay. Results: SHJKSmex pre-treatment at 300 mg/kg decreased infarct volume by 87% and mean brain water content by 90% of the MCAO control group. Moreover, SHJKSmex effectively suppressed the expression of inducible nitric oxide synthase, reactive oxygen species, interleukin 1, and caspases-8 and −9 and increased the B-cell lymphoma 2/Bcl-2-associated X protein ratio (Bcl-2/Bax) in ischaemic mouse brain. The hippocampal pyramidal cell densities were significantly increased in the 300 mg/kg SHJKSmex-administered group compared to the MCAO control group. Discussion and conclusions: SHJKSmex protected the brain from ischaemic stroke in mice through its antioxidant, anti-inflammatory, and antiapoptotic activities. Our findings suggest that SHJKSmex is a promising therapeutic candidate for the development of a new formulation for ischaemia-induced brain damage.